1989
DOI: 10.1021/bi00435a051
|View full text |Cite
|
Sign up to set email alerts
|

Magic angle sample spinning carbon-13 nuclear magnetic resonance of isotopically labeled bacteriorhodopsin

Abstract: Bacteriorhodopsin (bR), the light-driven proton pump protein from Halobacterium halobium, was biosynthetically labeled with [4-13C]Asp. The incorporation yield was 48%. The magic angle sample spinning (MASS) 13C nuclear magnetic resonance (NMR) spectrum of this sample revealed six different peaks superimposed on a broad band of naturally abundant peptide-bond 13C. Two of the six carbonyl signals can be attributed to internal-protonated Asp carboxyl groups, one of which might be Asp115. An additional resonance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
1

Year Published

1990
1990
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
5
39
1
Order By: Relevance
“…Again this can be explained by a protonation of Asp ss resulting in a new band at 169.5 ppm with an almost identical o~o as that found in the M intermediate. The signals of Asp ~ and Asp bzs now merge into one broad band due to the shift of the resonance of Asp ~s from 170.3 to 171 ppm, as previously shown [20]. Both residues are still protonated.…”
Section: Results and Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…Again this can be explained by a protonation of Asp ss resulting in a new band at 169.5 ppm with an almost identical o~o as that found in the M intermediate. The signals of Asp ~ and Asp bzs now merge into one broad band due to the shift of the resonance of Asp ~s from 170.3 to 171 ppm, as previously shown [20]. Both residues are still protonated.…”
Section: Results and Discussionsupporting
confidence: 66%
“…Three pronoun~d siti~nals are found in the ground state. They have forl~¢rly been assigned to the deprotonated Asp ~-~ (176.3 R)~m) and Asp ~s (173.7 ppm) as well as to the protonated i~sp ~ (170.3 ppm) [20][21][22]. These assignments made ~ls~ of FTIR studios [5] which showed that Asp b ~s is the ~ccnd internal protonated asparti¢ acid in the BR ~r~and state.…”
Section: Results and Discussionmentioning
confidence: 91%
See 3 more Smart Citations